Increased Vitamin D Levels Inhibit the Production of the Sleep Hormone - Awatif Ali Khalifa Khalfa; Ibrahim Mohamed Emhimed Ghriba (Journal of Scientific and Human Dimensions, 2026)
This research aims to study the relationship between vitamin D levels, melatonin production, and their impact on sleep quality. Studies suggest that increased vitamin D levels may negatively affect melatonin secretion, leading to sleep disorders such as insomnia and sleep fragmentation. Data from previous studies were analyzed to determine the extent of vitamin D’s influence on the sleep cycle. The findings indicate that excessive intake of vitamin D may disrupt hormonal balance, highlighting the need for a precise balance of its levels in the body. The study recommends further research to gain a deeper understanding of the underlying mechanisms while emphasizing the importance of medical awareness regarding appropriate vitamin D dosages to prevent adverse effects on sleep and overall health.
Keywords: Vitamin D; Melatonin; Sleep Disorders; Insomnia; Sleep Quality; Biological Clock; Hormones; Proper Dosage